Pelatihan Meningkatkan Daya Ingat Anak Pinggir Sungai Deli Melalui Pengembangan Minat dan Bakat - Andini Kartika Sari; Mia Aulina Lubis (Yayasan Literasi Sains Indonesia, 2023)
Education is something that must be done by every human being regardless of where the human comes from, regardless of the layers that exist in the midst of society. However, the problem in a learning process is the basic ability of a child to read and recognize letters due to the limited ability of a person to remember. On this occasion the practitioner found a self-supporting location called Sanggar Anak Sungai Deli which has the aim of empowering children on the banks of the Deli river. This children's studio fully supports education and self-development through the interests and talents of children on the banks of the Deli River, both from elementary school age and up to senior high school. The activities empowered by the management of the Deli Sungai Anak Studio include dance classes, reciting the Koran, knitting classes, music classes, multimedia classes and even other activities aimed at forming the interest and eating of the children on the banks of the Deli River. But what makes the practitioner interested in doing the second Field Work Practice here is, in the midst of the ability of the children on the banks of the Deli River in developing interests, talents and soft skills, it turns out that in terms of letter recognition there are still many who find it difficult to understand because of limited memory abilities, especially in young children. Many children aged 6-8 years do not know letters. Therefore, the purpose of the practitioner is to act as an intermediary in improving the memory of the children on the banks of the Deli River through developing the interests and talents that they live out daily at the Sungai Deli Children's Studio.